2021
DOI: 10.1007/s11356-021-17474-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of historical CMIP6 model simulations and future projections of temperature over the Pan-Third Pole region

Abstract: The Pan-Third Pole (PTP) region, which encompasses the Eurasian highlands and their surroundings, has experienced unprecedented, accelerated warming during the past decades. This study evaluates the performance of historical simulation runs of the Coupled Model Intercomparison Project (CMIP6) in capturing spatial patterns and temporal variations observed over the PTP region for mean and extreme temperatures. In addition, projected changes in temperatures under four Shared Socioeconomic Pathway (SSP) scenarios … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
(57 reference statements)
2
6
0
Order By: Relevance
“…Similarly, the simulated trade winds are relatively weak, whereas the strength of the westerlies is well simulated compared with the reference. These results are consistent with those of previous studies that showed CMIP multi-model ensembles have positive or negative biases on a regional scale with respect to the surface and lateral boundary variables for the historical climate but reasonably reproduce their spatial distribution (e.g., Kim et al 2020;Zhang et al 2020;Fan et al 2022).…”
Section: Evaluation Of Physical Quantity For Surface and Lateral Boun...supporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, the simulated trade winds are relatively weak, whereas the strength of the westerlies is well simulated compared with the reference. These results are consistent with those of previous studies that showed CMIP multi-model ensembles have positive or negative biases on a regional scale with respect to the surface and lateral boundary variables for the historical climate but reasonably reproduce their spatial distribution (e.g., Kim et al 2020;Zhang et al 2020;Fan et al 2022).…”
Section: Evaluation Of Physical Quantity For Surface and Lateral Boun...supporting
confidence: 92%
“…Numerous studies have examined the performance of CMIP6 models on global and regional scales (e.g., Eyring et al 2016;Kim et al 2020;Lee et al 2021;Planton et al 2021;Tang et al 2021;Xie et al 2022). CMIP6 models have been reported to realistically reproduce mean and extreme climates compared to observations, and their performances have improved compared to those of previous phase CMIP models (e.g., Kim et al 2020;Xie et al 2022;Fan et al 2022). These model evaluation studies have been mainly conducted in the atmospheric fields connected with the international regional-atmosphere climate model project known as the COordinated Regional climate Downscaling EXperiment (CORDEX; Oh et al 2014;Torres-Alavez et al 2021), and model performances have often been evaluated based on habitable land areas rather than the ocean region (e.g., Kim et al 2020;Xie et al 2022;Fan et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive studies have been conducted on evaluating and projecting extreme climate change over ACA. The prediction studies of temperature and temperature converge, with a significant warming trend expected for the 21st century [20,[35][36][37], while the simulation and prediction of extreme precipitation are more uncertain [9,38]. Li et al [27] showed that almost all models (HighResMIP) overestimated the precipitation frequency in CA, with a greater overestimation of the precipitation frequency and amount in mountainous areas.…”
Section: Introductionmentioning
confidence: 99%
“…Chen & Zhou, 2016;Sharmila et al, 2015). All models project that the TP surface temperature will continue to increase under future warming climate (e.g., Fan et al, 2022;Guo et al, 2016;F. Su et al, 2013), but consensus on its future warming magnitude remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Climate models are widely used to study the future projections of climate change (e.g., Beniston et al., 2007; X. Chen & Zhou, 2016; Sharmila et al., 2015). All models project that the TP surface temperature will continue to increase under future warming climate (e.g., Fan et al., 2022; Guo et al., 2016; F. Su et al., 2013), but consensus on its future warming magnitude remains lacking. The magnitude of temperature increase could be influenced by emission scenarios (Tian et al., 2015; You, Cai, Wu, et al., 2021; M. Zhou et al., 2022), with the projected difference between the very high and very low emission scenarios reaching as much as 6°C by the end of the 21st century (Y. Peng et al., 2022).…”
Section: Introductionmentioning
confidence: 99%